STRATEGI PENGEMBANGAN KURIKULUM BAHASA ARAB MA NURUL ISLAM TENGARAN DALAM MENJAWAB TUNTUTAN STUDY LANJUT TIMUR TENGAH - Purwoko (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to describe and analyze the development of the Arabic language curriculum at Madrasah Aliyah Nurul Islam Tengaran in response to the demands of further studies in Middle Eastern universities. This study was conducted using a qualitative descriptive approach. Data collection techniques are carried out through interviews, observations and documentation. Data analysis using phenomenological analysis involves drawing conclusions based on data obtained from the field and the objectives of the research. The results of the study show that: (1) The development of the Arabic language curriculum is carried out comprehensively, covering academic and non-academic fields, the creation of a conducive environment, and the improvement of facilities and infrastructure, (2) Arabic language proficiency, which includes the aspects of kitabah (writing), muhadathah (speaking), qira’ah (reading), and istima’ (listening), is integrated within a holistic management system combining both the school (madrasah) and Islamic boarding school (pesantren) approaches, (3) The stages of the development strategy include: (a) SWOT analysis of the institution as a scientific vision, (b) needs analysis (Tracer Study), (c) determination of graduate profiles, and (d) formulation of learning outcomes. This comprehensive strategy, integrating cognitive and psychomotor abilities as reflected in the research findings, could serve as an alternative method to strengthen students' Arabic language proficiency in various educational institutions.